PERANCANGAN MEDIA VIDEO DESAIN INTERIOR SEBAGAI SALAH SATU PENUNJANG PROMOSI DAN INFORMASI DI PT. WANS DESAIN GROUP - Wahyu Hidayat; Fauzi Maafuf; Saeful Bahari (UNIVERSITAS RAHARJA, 2016)
Interior design and decoration for this often happens in common where both of them like in a the same profession. Because they both have the same i.e. want to give a sense of sense of beauty and comfort in every room. The Interior decoration is only a small part of the task is an interior designer. Interior designers and interior decorators alike have an important role in the enhancement of the quality of the room, although both are different. As for the field that will be needed at a company or organization to design a promotional media in promoting and informing a product item or service to the community. So the company becomes taxable in the community and in promoting a product or a simulation of the design you want. To promote it field examples like design, Interior, Multimedia, and animations.